Analisis Persepsi Stakeholder atas Laporan Sustainability - Janssen Rantelangi; Ratna Ayu Damayanti; Sri Sundari (Accounting Department, Faculty of Economics and Business, Universitas Hasanuddin, 2023)
The triple bottom line paradigm in industrialization has encouraged companies to implement and disclose their social and environmental performance as well as their financial performance. This study aims to analyze the perceptions of PT Vale's external stakeholders, namely the people of Nuha District and NGOs engaged in social and environmental fields, about the legitimacy of PT Vale through its CSR program as disclosed in the PT Vale Sustainability Report. The data used in this study are primary data sourced from direct statements from NGOs and the community which were collected using in-depth interview techniques. The results of data collection were analyzed by qualitative methods using a descriptive approach. The results of the study illustrate that there is a congruence between stakeholder’s expectations and PT Vale's performance through the CSR program. However, there is still a dominant gap in the legitimacy of PT Vale's CSR as disclosed in PT Vale's Sustainability Report.